Continuous Monitoring of Vital Signs After Hospital Discharge: A Feasibility Study - Nicharatch Songthawornpong; Thivya Vijayakumar; Marie Said Vang Jensen; Mikkel Elvekjaer; Helge B. D. Sørensen; Eske K. Aasvang; Christian S. Meyhoff; Vibeke R. Eriksen (Patient Safety)
# Introduction